2019
DOI: 10.1093/migration/mnz042
|View full text |Cite
|
Sign up to set email alerts
|

Does mentoring make immigrants more desirable? A conjoint analysis

Abstract: High levels of immigration to Germany have led to increased interests in integration programs. Yet, it is unclear to what extent immigrant participation in integration programs affects attitudes toward immigrants among the host population. This article measures which immigrant attributes German respondents find desirable, and how these features interact with participation in a mentoring program with a local mentor. Mentoring is often employed to aid immigrant integration and typically focuses on psychosocial, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 34 publications
0
10
0
Order By: Relevance
“…In the literature, this has been interpreted as respondents thinking in sociotropic terms, meaning about what migrants are more likely to contribute to society. This seems to be the case almost regardless of own position in society (Hainmueller & Hopkins 2015; Reeskens & van der Meer 2019; Weiss & Tulin 2019). We can also see that gender does not matter, but being a Muslim or Hindu migrant carries a penalty to the chance of being granted permanent residency, compared to a Christian candidate.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…In the literature, this has been interpreted as respondents thinking in sociotropic terms, meaning about what migrants are more likely to contribute to society. This seems to be the case almost regardless of own position in society (Hainmueller & Hopkins 2015; Reeskens & van der Meer 2019; Weiss & Tulin 2019). We can also see that gender does not matter, but being a Muslim or Hindu migrant carries a penalty to the chance of being granted permanent residency, compared to a Christian candidate.…”
Section: Resultsmentioning
confidence: 99%
“…For instance, Hainmueller and Hopkins (2015) find that in the United States, there is a consensus around the idea that compared to a migrant seeking to be reunited with his or her family, a job‐seeking migrant is less welcome, while a migrant escaping persecution is more welcome. In the German context, Weiss and Tulin (2019) have shown that compared to a migrant seeking a better job, family reunion and humanitarian migrants are more welcome, while economic migrants are perceived no differently. Similarly, Reeskens and van der Meer (2019) show that in the Netherlands, political refugees are more welcome, while economic migrants are less welcome.…”
Section: Literature and Theorymentioning
confidence: 99%
See 2 more Smart Citations
“…Based on a quasi-experimental design testing diversified mentoring relationships between primarily white management-student mentors and newly resettled refugees in the United States, they find that even short-duration mentoring may be powerful in increasing the cultural intelligence and empathy of mentors. A recent study by Weiss and Tulin (2019) also showed that immigrant participation in a mentoring program can improve the attitudes towards them among the host population. They conducted an experiment in which German respondents are presented with two immigrant profiles, and they need to decide which they would prefer to come to live in their municipality.…”
Section: The Mentor's Perspectivementioning
confidence: 98%